204 HPV education and vaccination in a public hospital in brazil. (18th September 2019) - Santos, C; Azevedo, C; Sales, J; Mello, J
Abstract : Objectives: Official statistics reports a low HPV vaccination rate in Brazilian teenagers. Education about HPV vaccination is considered an area for improvement and our aim was increase the number of patients educated about the importance of HPV vaccination thus improving the HPV vaccination rate. Methods: Between September 2018 and December 2018, in the Oncology Department at IMIP, we undertook a structured approach to educate the female cancer patient about HPV and its relationship with cervical cancer with support from ASCO's Quality Training Program. Our team used standard plan-do-study-act (PDSA) methodology to achieve our goal of increase by 50% the number of patients educated about the importance of HPV vaccination. We also analyzed rate of HPV vaccination at our institution before and after this intervention. Results: Before October 2018 a mean of 1263 female cancer patients were consulted at IMIP per month and none were educated about HPV vaccination. After our PDSA1 we had a mean of 1087 female cancer patients consulted per month, and we educated about 16% of them. We had no improvement in the HPV vaccination rate. Before October 2018 there was a mean of 39 teenagers vaccinated per month, an after, a mean of 20. Conclusions: After one cycle of PDSA, we have increased our patient education, however there was no improvement in the vaccination rate at IMIP. Maybe, as IMIP is a tertiary center, we could not observe such changes, but primary health services rates of vaccination may reflect better the impact of this intervention.